Implementation of a script for predonation interviews: impact on human immunodeficiency virus risk in South African blood donors. Issue 7 (4th April 2019) - Mitchel, Josephine; Custer, Brian; Kaidarova, Zhanna; Murphy, Edward L.; van den Berg, Karin; ,
Abstract : BACKGROUND: The way in which the donor history questionnaire is conducted plays a crucial role in the self‐disclosure of behavioral risk factors for human immunodeficiency virus (HIV) infection by prospective donors. The South African National Blood Service changed its policy on the process of donor assessment in May 2015 by implementing a compulsory interviewer script used to assess donor eligibility. STUDY DESIGN AND METHODS: A pre‐ and postevaluation study to determine the impact of scripted interviews on high‐risk deferrals and recently acquired HIV infections. We used historical data to compare 18 months before and after the implementation of the script. RESULTS: We recorded a total of 3, 169, 656 donor presentations during the two 18‐months periods, of which 52.2% (1, 655, 352) were made during the scripted period. A multivariable logistic regression analysis adjusting for donor and demographic characteristics found the odds of high‐risk deferral to be slightly greater (odds ratio [OR], 1.06; 95% confidence interval [CI], 1.05‐1.07) during the scripted period. A separate multivariate logistic regression model, also adjusting for donor and demographic characteristics, showed that the odds of recently acquired HIV infection were significantly lower (OR, 0.88; 95% CI, 0.79‐0.97) during the scripted period. CONCLUSION: This study showed that implementation of a scripted interview was associated with increased HIV risk deferral and decreased recent HIV infection. This study indicates potential improvement in blood safety with the implementation of a scripted donor interview and has relevance to blood safety in other sub‐Saharan African countries.